Pharmacological Correlates of Jalaukavacharana: An Integrative Review of Leech Salivary Secretome Bioactivity in Classical Shalya Tantra Indications for Rakta-Dushti Disorders - A. S, Anitha (Journal of Neonatal Surgery, 2025)
Background: Jalaukavacharana, the therapeutic application of medicinal leeches, occupies a uniquely detailed position among the five classical methods of Raktamokshana. Acharya Sushruta devotes an entire chapter of Sutrasthana to leech classification, technique, and disease specific indication. Leech therapy has undergone a parallel clinical revival in contemporary medicine and is now an established adjunct in microsurgical and reconstructive practice, principally for relief of post-operative venous congestion. The therapeutic action in both traditions converges on the leech salivary secretome, a complex mixture of anticoagulant, antiplatelet, fibrinolytic, and anti-inflammatory bioactive molecules released during feeding. Objective: This review correlates individually named Shalya Tantra indications for Jalaukavacharana with the specific salivary bioactive compounds plausibly responsible for the corresponding therapeutic effect, an exercise not previously undertaken in a structured, evidence graded format and not addressed by the single existing Ayurveda-biomedicine review of leech therapy. Methods: A narrative and integrative review was conducted across PubMed, Scopus, Web of Science, the DHARA database, and the Cochrane Library, combined with manual reference screening of secondary Ayurvedic literature. Classical Sthana, Adhyaya, and Shloka citations were verified directly against primary published editions and, wherever available, against a second independently published secondary source citing the same edition; one citation that could not be corroborated on this verification was removed from the review. Sources were organised narratively into three domains, classical classification and indication, salivary compound pharmacology, and a qualitative convergence mapping between the two, following a synthesis approach informed by the reverse pharmacology framework applied elsewhere in Ayurveda-biomedicine integrative research. Reporting follows the SANRA criteria for narrative review articles. Results: Twelve classically described leech types were identified, six Nirvisha and six Savisha, of which the six Nirvisha types are described as therapeutically usable. Five principal salivary bioactive classes were characterised in the modern literature, namely hirudin, hyaluronidase, calin, destabilase, and the Bdellin and Eglin protease inhibitor family, each with an increasingly well defined mechanism of action. A convergence analysis mapping six major classical indications to their most plausible salivary correlate showed strong mechanistic alignment for Vatarakta (hirudin mediated anticoagulation) and Shotha (hyaluronidase mediated interstitial spreading), with moderate to weak alignment for Kushtha, Visarpa, Netra Roga, and Shirashula, reflecting the more multifactorial classical pathophysiology of these conditions. Conclusion: The disease specific prescriptions for Jalaukavacharana recorded in Shalya Tantra texts show a coherent, though not yet experimentally confirmed, correlation with the molecular pharmacology of the leech salivary secretome. This convergence provides a structured, testable framework for future comparative secretome research across the classically described Nirvisha leech types and for indication specific clinical evaluation